Intercultural Communication Between Traders And Buyers In Padang Panjang Culinary Market - Roem, Elva Ronaning; Istiyanto, S.Bekti; Sarmiati, Sarmiati; Vanisya, Winda (Mediator: Jurnal Komunikasi, 2024)
The province of West Sumatra offers a variety of tourist attractions, one of which is the contemporary culinary scene in Padang Panjang. This city attracts visitors from various regions within West Sumatra as well as from outside the province. The diversity of culinary offerings, including both traditional and modern dishes, makes Padang Panjang a popular culinary destination. This research aims to explore tourists' perceptions of the night culinary market in Padang Panjang, which has become one of the city's main attractions. The study uses a qualitative approach to delve into the dynamics of communication between traders and customers at the market. Data was collected through direct observation, interviews with traders and visitors, and document analysis. The research findings show that the harmony of interactions at the culinary market is achieved through various communication strategies, including intercultural, interpersonal, and non-verbal communication. The study identifies two prominent communication patterns: the use of easily understood language and smiling as practical strategies to connect traders and customers from diverse backgrounds. Tourists' perceptions of the culinary market indicate that the food stalls offer high-quality food, which leaves them satisfied and eager to return.